STRUKTUR MODAL MEMEDIASI HUBUNGAN ANTARA PROFITABILITAS, UKURAN PERUSAHAAN, DAN SALES GROWTH TERHADAP HARGA SAHAM - Soniya Oktaviyanti Kartini (2021)
This purpose of this study is to examine the effect of profitability, firm size, and sales growth on stock prices and capital structure. This study uses 49 sample data of property, real estate, and building construction companies listed on the Indonesia Stock Exchange in 2017-2019 with purposive sampling method. The analytical technique used is the classical assumption test, descriptive statistical analysis, hypothesis testing, and multiple linear analysis using SPSS 23. The results show that profitability and sales growth have no significant effect on capital structure, while firm size has a positive and significant effect on capital structure. Furthermore, profitability, company size, sales growth, and capital structure have no significant effect on stock prices. In addition, indirectly profitability, company size, and sales growth through capital structure have no significant effect on stock prices.